Proceedings of the 9th European Software Engineering Conference Held Jointly With 10th ACM SIGSOFT International Symposium on F 2003
DOI: 10.1145/940103.940104
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating redundancies with a "composition with adaptation" meta-programming technique

Abstract: Redundant code obstructs program understanding and contributes to high maintenance costs. While most experts agree on that, opinions -on how serious the problem of redundancies really is and how to tackle it -differ. In this paper, we present the study of redundancies in the Java Buffer library, JDK 1.4.1, which was recently released by Sun. We found that at least 68% of code in the Buffer library is redundant in the sense that it recurs in many classes in the same or slightly modified form. We effectively eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…StrutsBox is an Eclipse [7] plug-in for developing applications with Apache Struts Framework (http://struts.apache.org/). Its central component is a visual editor that graphically shows the flow of information in web applications.…”
Section: An Overview Of the Case Study Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…StrutsBox is an Eclipse [7] plug-in for developing applications with Apache Struts Framework (http://struts.apache.org/). Its central component is a visual editor that graphically shows the flow of information in web applications.…”
Section: An Overview Of the Case Study Systemmentioning
confidence: 99%
“…Its central component is a visual editor that graphically shows the flow of information in web applications. Apache Struts is an open source framework for developing Java Web Application [7]. It uses MVC (Model -View -Controller) architecture (http://en.wikipedia.org/ wiki/Model-view-controller), where Model represents the business logic, View represents the user-interface, and Controller represents the navigational code.…”
Section: An Overview Of the Case Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In our studies of new, well-designed programs, we typically found 50%-90% of code contained in such similar program structures, repeated many times (often called clones in the literature). For example, the extent of the redundant code in Java Buffer library was 68% [6], in parts of STL (C++) -over 50% [1], in J2EE Web Portals -61% [12], and in certain ASP Web portal modules -up to 90% [9]. The last two results are from the projects at STEE in which XVCL was applied to combat the problem of counterproductive repetitions.…”
Section: Figure 1 An Operational Scenario In Cad System For Policementioning
confidence: 99%
“…Code clones often hint at the existence of design-level similarity patterns in a program (or across programs). Such large granularity similarity patterns -we call them "structural clones" -signify reuse opportunities that, if properly exploited, could lead to simpler, easier to maintain, and more reusable program solutions [19]. The reasons why clones appear in source code have been analyzed [6][14] [20] and clone detection tools have been proposed [1] [6][14] [21].…”
Section: Introductionmentioning
confidence: 99%